2020
DOI: 10.1111/joss.12568
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of extrinsic cues on consumers' evaluation of red wine using a projective mapping task

Abstract: Consumers' perception (intrinsic sensory characteristics) of wine can be affected by extrinsic cues. This study aimed to determine the influence of extrinsic cues (price and label information/bottle) on consumers' sensory perception of red wine blends.A total of 202 participants (regular consumers of red wine), evaluated six red wine blends. Projective mapping (PM) and ultra-flash profile (UFP) were used to characterize the wines in three separate sessions: blinded, presented with the bottle, and presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The first dimension separated the wines based on bitter, peppery, dry, and medium body on the positive side, with sweet, fruity, cranberry, and red fruit on the negative side. This separation agrees with a past study that found that the NS red wines could be separated based on sweet, fruity, bitter, and peppery attributes (Jantzi et al, 2020). On the second dimension, all the wines presented with ingredient lists (W1IL, W2IL, and W3IL) were on the positive side and were associated with sweet, floral, fruity, and dried fruit.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The first dimension separated the wines based on bitter, peppery, dry, and medium body on the positive side, with sweet, fruity, cranberry, and red fruit on the negative side. This separation agrees with a past study that found that the NS red wines could be separated based on sweet, fruity, bitter, and peppery attributes (Jantzi et al, 2020). On the second dimension, all the wines presented with ingredient lists (W1IL, W2IL, and W3IL) were on the positive side and were associated with sweet, floral, fruity, and dried fruit.…”
Section: Resultssupporting
confidence: 93%
“…These methods are also a convenient alternative to descriptive analysis, as they can quickly assess differences in the samples (Liu, Grønbeck, Di Monaco, Giacalone, & Bredie, 2016). Furthermore, PM and UFP have been used in a variety of different studies to assess the sensory attributes of wine (Fariña et al, 2015; Hopfer & Heymann, 2013; Jantzi, Hayward, Barton, Richardson, & McSweeney, 2020; Kemp, Pickering, Willwerth, & Inglis, 2018; Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Researching different target consumers' evaluation of wine under conditions of full sensory (intrinsic) and non-sensory (extrinsic) information disclosure, has gained traction within the wine sector in recent years (Sogari et al, 2019). In wine marketing, differences in perceived preferences and expectations between blind and full conditions of the product may often be influenced by extrinsic attributes such as the brand name or region of origin (Jantzi et al, 2020). These expectations can influence the consumer's conscious response to a particular wine, however, might not have the same effect on the consumer's subconscious response (Lockshin and Corsi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Kemp et al (2018) noted that PM is suited to a wine industry context because of its spontaneous aspect and its flexibility. Additionally, Lawrence et al (2013) espouse a “free comments” method for wine professionals stating that “methods classically used for sensory analysis appear to be poorly suited to a professional wine panel, which has less time available than other panel types.” Jantzi, Hayward, Barton, Richardson, and McSweeney (2020) have recently applied the method even in the context of extrinsic cues consumers receive for red wines (such as price and information/bottle).…”
Section: Introductionmentioning
confidence: 99%